2013
DOI: 10.2355/isijinternational.53.170
|View full text |Cite
|
Sign up to set email alerts
|

Viscous Behavior of Alumina Rich Calcium-Silicate Based Mold Fluxes and Its Correlation to the Melt Structure

Abstract: The substitutional effect of SiO2 with Al2O3 content on the viscosity in the calcium-silicate melt-based system containing 12 mass% Na2O and 5 mass% Li2O was studied. Additions of Al2O3 increased the viscosity and higher Al2O3 concentrations modified the dominant silicate network into complex alumino-silicates with the aluminate structure becoming particularly prevalent at an Al2O3 content of 20 mass% and higher. FTIR (Fourier transform infra red) and Raman analysis showed increased amounts of symmetric Al-O 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 22 publications
(28 reference statements)
3
51
0
Order By: Relevance
“…In addition, it was confirmed by Kim et al measurement that the melt viscosity decreased by adding a small amount of Li 2 O into mold flux. [12] Also, experimental results of Liu et al [38] demonstrated that more faceted crystal precipitated by increasing Li 2 O content in mold fluxes within a reasonable amount, which is in accordance with our present findings.…”
Section: E Effect Of Melt Composition On Crystal Morphologysupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, it was confirmed by Kim et al measurement that the melt viscosity decreased by adding a small amount of Li 2 O into mold flux. [12] Also, experimental results of Liu et al [38] demonstrated that more faceted crystal precipitated by increasing Li 2 O content in mold fluxes within a reasonable amount, which is in accordance with our present findings.…”
Section: E Effect Of Melt Composition On Crystal Morphologysupporting
confidence: 93%
“…As a result, to develop an optimized unreactive CaO-Al 2 O 3 -based mold flux, the second strategy, is increasingly investigated by many researchers. [3,4,[8][9][10][11][12] Blazek et al [3] worked on lime-alumina-based mold flux for casting high-Al AHSS steel and showed that the interaction was markedly reduced and the as-cast slab quality was improved compared to that of lime-silica-based mold flux. Cho et al [8] carried out casting trials of high-Al TRIP steel by using the newly developed lime-alumina-based mold fluxes, and their results suggested that mold heat transfer in casting process and surface quality of slab were improved, compared to that of lime-silica-based mold fluxes as well.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the addition of MnO as a network modifier could increase the amount of O − and depolymerize the complex network structures of the molten slag, then decreasing the viscosity. On the other hand, the high Al 2 O 3 content of the present slag system may increase the quantity of complex aluminate or alumino-silicate structural units, 20) and a dynamic balanced reaction as shown in Eq. (2) may exist in the slag.…”
Section: )mentioning
confidence: 99%
“…Al 2 O 3 , which is known to be an amphoteric oxide, can generally be considered to behave as a network forming oxide in the absence of significant acidic components such as SiO 2 similar to the present TiO 2 -MnO-Al 2 O 3 -8.64ZrO 2 -2.77Na 2 O flux system. 19,20) The general trend shows the viscosity decreases with increasing (TiO 2 +1.13MnO)/Al 2 O 3 and again seems to be more pronounced at lower temperatures, where complex network structures are prevalent in the absence of significant thermal energy, which can then be modified with compositional changes in the flux. With increased extended basicity and assuming full depolymerization is nearly reached, where complex network structures no longer exist, the viscosity seems to converge to approximately 0.03 Pa·s.…”
Section: Melt Structure Analysis Using Raman and Xpsmentioning
confidence: 99%